Electrical and electrothermal de-icing performance for biodegradable graphene/polyhydroxyalkanoates and graphene/polylactic acid composites - Yijun Liao; Libo Wan; Ting Yin; Yunyi Li; Xiaoli Wu (eXPRESS Polymer Letters)
The electrical and electrothermal de-icing performance of graphene/polyhydroxyalkanoates (PHA) and graphene/polylactic acid (PLA) composites with different thicknesses were systematically compared and investigated. Graphene/PHA with 1 mm thickness shows a slightly lower electrical resistivity than graphene/PLA. However, the results are contrary for 0.1 mm-thick samples, likely due to poorer interfacial adhesion between graphene and PHA. Besides, all 0.1 mm-thick samples show higher electrical resistivity than 1 mm-thick samples, likely attributed to the alignment of graphene. The current-voltage curves of graphene/PHA exhibit nonlinear behavior with fluctuations, whereas all graphene/PLA samples show linear behavior. This result enables the graphene/PLA to exhibit superior electrothermal stability than graphene/PHA. An excellent electrothermal performance is obtained for these composites. The temperature increases from –40.2 to 95 °C within 17 s under 7 V. While these composites cannot be self-heated and utilized above 95 °C, this is because the composites would undergo electrical breakdown when heated to temperatures above 95°C for 5~10 s. The composite can melt ice within 550 s at –40 °C and within 447 s at –20 °C. These findings suggest that graphene/PHA and graphene/PLA composites hold significant potential for de-icing applications.